Pembuatan Video Edukasi untuk Meningkatkan Kesadaran Masyarakat Mengenai Rasisme di Indonesia - Theodesia Lady Pratiwi; Rusman Rusman; Charlie Charlie; Michael Angelo; Lilis Criestina; Hendro Hendro; Ricky Wibowo; Jenny Purnama; Naida Aisyah Alima; Gracia Vania Suhartono (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Diversity of religions, tribes, and races in Indonesia make Indonesia as a unique and rich country, but it also causes some disputes. It is not one or two times the disputes emerges. This indicates that Indonesians have lack of knowledge about racism and harmonization and how to maintain harmony by respecting and tolerating others. Thus, education on racism and harmonization is urgently needed. This study is going to design or create an educational video that is uploaded to YouTube that is expected to be able to increase people awareness on racism and harmonization. YouTube is chosen because it is easily accessed. The educational video got positive responds that stated that the video can enrich knowledge and increase the awareness on racism and harmonization. This may because the video outlines unique and interesting explanation through the animation and the video is easy to understand.